METHODS AND MEANS OF AUTOMATED MONITORING OF COMPLEX CONTOURED SURFACES IN FOUNDRY AND METALLURGICAL PRODUCTIONS - A. P. Markov; V. F. Gogolinsky; A. A. Azarko; E. M. Patuk (Литьë и металлургия)
The models of interrelations of emissions with surfaces and ways of transformation of revealed technological characteristics in commutated structure of pneumatic-optical conversions are considered.